Formulation and Characterization of Vaginal Capsules and Tablets Providing Fast Release of Live Lactobacillus spp. - Aleksovski, Aleksandar; Hosseini, Haniehsadat; Alkhafaji, Hajar; Leite, Michaëla; Sagasta, Ander; Leopold, Viviane (Archives of Pharmacy, 2025)
Live biotherapeutic products (LBPs) are gaining significant medical importance as a new approach in the prevention and treatment of various conditions in the female population. This study investigated the design, development, and evaluation of immediate-release (IR) vaginal dosage forms containing live Lactobacillus spp., with the aim of enabling fast and effective drug delivery in the vaginal environment. Capsule and tablet formulations were developed using different excipients and appropriate manufacturing processes (encapsulation and direct compression) and systematically evaluated for their robustness and performance. The results demonstrated that all capsule formulations exhibited suitable flowability and uniformity of dosage units, with hard gelatine capsules (HGC) providing the most favourable disintegration times compared to hydroxypropyl methylcellulose (HPMC) and pullulan capsules. Tablet formulations based on microcrystalline cellulose (MCC) achieved optimal hardness, friability, and disintegration, especially under lower compression forces, confirming MCC’s multifunctional role as a filler, binder, and disintegrant. Importantly, both dosage forms maintained Lactobacillus viability with only minor losses (~0.5 log), preserved the acidic vaginal environment (pH 4.2), and demonstrated robustness under simulated biorelevant conditions. These findings highlight that IR vaginal capsules and tablets can be effectively tailored to deliver live biotherapeutics with rapid onset of action, thereby advancing microbiome-based strategies for women’s health.
Keywords: vaginal drug delivery; live biotherepeutic products; immediate release; capsule; tablets